PENGARUH METODE MURI-Q (MUROTTAL IRAMA QUR’AN) TERHADAP PENINGKATAN MOTIVASI HAFALAN SISWA DI SD MUHAMMADIYAH BEDOYO - Iswan Iswan (PGSD Universitas Muhammadiyah Cirebon, 2022)
This research is motivated by the low motivation of students in learning tahfidz. Students feel bored quickly and quickly forget memorization because teachers who still use the lecture method, the teacher only gives orders without providing a solution for how to memorize a fast and fun method. This study aims to increase students' motivation in memorizing short suras using the Muri-Q (Murattal Irama Qur'an) method. The method used in this research is experimental research with a pre test post test control group design approach. The results showed that there was an effect of the Muri-Q method on increasing students' motivation in memorizing short suras. This is evident from the results of the N-Gain test and t test, with the average value of the experimental class pre-test and post-test results of 75% and is included in the quite effective category. And the results of the t-test of 9.079> 1.697 and the value of Sig. of 0.000 < 0.05. This means that there is an effect of increasing students' motivation to memorize using the Muri-Q method. Keywords: Motivation, MURI-Q, Tahfidz.